Modified polyester fiber
By graft polymerizing ethylenically unsaturated organic acids with specific alkyl esters in polyester fibers, the fibers achieve enhanced hygroscopicity and deodorizing properties, overcoming structural limitations and cost inefficiencies in traditional modifications.
Patent Information
- Application Number
- JP2023110270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Existing polyester fibers with carboxyl groups have a dense structure, limiting their functionality improvements despite modification attempts, such as hygroscopicity and deodorizing properties.
Incorporating a specific alkyl ester compound during graft polymerization of ethylenically unsaturated organic acids within polyester fibers, enhancing the graft polymerization rate and functionality, particularly with compounds like 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and diisobutyrate.
The modified polyester fibers exhibit significantly improved moisture absorption and deodorizing properties, achieving high graft polymerization rates while reducing chemical costs and maintaining color fastness.
Smart Images

Figure 2025008267000005 
Figure 2025008267000006 
Figure 2025008267000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified polyester fiber having a carboxyl group and a textile product using the same, and in particular to a product which has been modified by a high graft polymerization rate and has achieved improved functionality by containing a specific alkyl ester compound. [Background technology]
[0002] It has been known for some time that carboxyl groups can be introduced into polyester fibers to enhance functionality such as moisture absorption and deodorization (see, for example, Patent Documents 1 and 2). However, polyester fibers are highly crystalline, and even if they are modified by introducing carboxyl groups to form loose structural portions, they still have a fine and dense structure, so there is a certain limit to the improvement of functionality. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-69844 A [Patent Document 2] JP 2017-14641 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been devised in view of the current state of the prior art, and aims to provide a modified polyester fiber that can achieve modification through a high graft polymerization rate, which has been difficult to achieve in the past, and can achieve high functionality improvement even with a graft polymerization rate at the same level as in the past, and a textile product containing the same.
[0005] Means for Solving the Problems The present inventors have conducted intensive research in order to achieve the above object, and as a result have discovered that the fiber modification effect achieved by graft polymerization can be dramatically enhanced by incorporating a specific alkyl ester compound into polyester fibers in which an ethylenically unsaturated organic acid has been polymerized inside the fibers, thereby completing the present invention.
[0006] That is, the present invention has the following configurations (1) to (8). (1) A modified polyester fiber, which is a polyester fiber in which an ethylenically unsaturated organic acid is polymerized inside the fiber, and which contains 25 to 10,000 ppm of an alkyl ester compound of an aliphatic carboxylic acid and / or an aromatic carboxylic acid. (2) The modified polyester fiber according to (1), wherein the ethylenically unsaturated organic acid is (meth)acrylic acid. (3) The modified polyester fiber according to (1), characterized in that the alkyl ester compound is at least one compound selected from the group consisting of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, and di-2-ethylhexyl phthalate. (4) The modified polyester fiber according to (1), characterized in that an ethylenically unsaturated organic acid is polymerized inside the fiber so that the mass increase rate due to polymerization is 5 to 60 mass %. (5) The modified polyester fiber according to (1), characterized in that the extraction pH is 4 to 10. (6) The modified polyester fiber according to (1), characterized in that the moisture absorption rate in an environment of 20°C and 65% RH is 3 to 30%. (7) The modified polyester fiber according to (1), characterized in that the deodorizing rate of acetic acid is ≧90%, the deodorizing rate of isovaleric acid is ≧90%, and the deodorizing rate of ammonia is ≧90%. (8) A textile product comprising 5% by mass or more of the modified polyester fiber according to any one of (1) to (7). Effect of the Invention
[0007] The modified polyester fiber of the present invention can achieve a high graft polymerization rate, which has never been achieved before, by increasing the reaction rate of the functional monomer, and can reduce chemical costs. Even if the modification rate (graft polymerization rate) is the same, the functionality can be dramatically improved by having a specific alkyl ester compound present in the fiber. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 shows the calibration curve for standard TMPDB. [Diagram 2] FIG. 2 shows the m / z 71 extracted ion chromatogram of modified fiber 1 of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The modified polyester fiber of the present invention is a polyester fiber whose functionality has been modified by polymerizing an ethylenically unsaturated organic acid inside the fiber, and is preferably a fiber modified by graft-polymerizing an ethylenically unsaturated organic acid onto a polyester fiber. Since the ethylenically unsaturated organic acid has a carboxyl group, the functionality of the fiber, such as moisture absorption rate and deodorizing property, can be improved by polymerizing the ethylenically unsaturated organic acid inside the fiber.
[0010] The polyester used as the fiber of the present invention is not particularly limited as long as it is a fiber-forming polyester. Examples of the main carboxylic acid component of the polyester include terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid, and examples of the main glycol component include ethylene glycol, propylene glycol, and tetramethylene glycol. As the polyester, for example, those containing linear polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polyethylene isophthalate, polybutylene terephthalate, or polyethylene 2,6-naphthalate as the main component are preferable, and polyethylene terephthalate is particularly preferable.
[0011] Depending on the application, the polyester may be copolymerized with a compound having functionality such as flame retardancy, dyeability, antistatic property, etc., or may contain additives such as a dulling agent, inorganic particles, etc.
[0012] In the present invention, the method of polymerizing an ethylenically unsaturated organic acid inside a fiber may, for example, be a method of absorbing an ethylenically unsaturated organic acid (monomer) having an unsaturated group such as a vinyl group into a polyester and polymerizing the monomers at least inside the polyester fiber. It is preferable to graft polymerize the monomer onto the polyester molecular chain to modify the fiber properties. In the present invention, such a method of polymerizing an ethylenically unsaturated organic acid inside a polyester fiber to modify the fiber is called "graft polymerization".
[0013] Examples of ethylenically unsaturated organic acids used in graft polymerization onto polyester include ethylenically unsaturated organic acids having a carboxyl group, such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, crotonic acid, and butene tricarboxylic acid; styrene sulfonic acid, and the like; among these, ethylenically unsaturated organic acids having a carboxyl group are preferred. Each of these can be used alone or as a mixture of two or more types for graft polymerization. As the ethylenically unsaturated organic acid, acrylic acid and / or methacrylic acid are particularly preferred. It is also possible to allow an ethylenically unsaturated monomer other than the ethylenically unsaturated organic acid to coexist. Examples of these ethylenically unsaturated monomers include compounds that can impart various functionalities, such as unsaturated organic acid esters, fluorine or bromine substitution products thereof, and phosphorus or sulfur-containing compounds.
[0014] The present invention is characterized in that an alkyl ester compound of an aliphatic carboxylic acid and / or an aromatic carboxylic acid is contained in the polyester fiber. This allows a high graft polymerization rate that has not been achieved so far to be achieved, thereby improving functionality, or allows high functionality to be expressed even with the same graft polymerization rate as before. Examples of the alkyl ester compound of an aliphatic carboxylic acid and / or an aromatic carboxylic acid include di-2-ethylhexyl phthalate (DEHP), 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate TMPMB (Texanol), and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate TMPDB (TXIB), which are shown by the chemical formulas below. It is preferable to use 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and / or 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, which are alkyl ester compounds of aliphatic carboxylic acids.
[0015] Di-2-ethylhexyl phthalate (DEHP) TIFF2025008267000001.tif44135
[0016] 2,2,4-Trimethyl-1,3-pentanediol monoisobutyrate (TMPMB) TIFF2025008267000002.tif81139
[0017] 2,2,4-Trimethyl-1,3-pentanediol diisobutyrate (TMPDB) TIFF2025008267000003.tif41142
[0018] The method of incorporating an alkyl ester compound of an aliphatic carboxylic acid or an aromatic carboxylic acid into polyester fibers can be achieved by adding these compounds in the process before the production of a textile product, thereby improving the functionality of the fibers, such as moisture absorption and deodorization. As a method of imparting the compounds in each process, the compounds may be kneaded during fiber production, or may be attached to the fibers and then heat-treated, or may be incorporated into the fibers by an exhaustion method. As a specific example, in the case of a cotton form, the compounds may be exhausted using an Obermeyer dyeing machine, or may be applied by spraying or the like and then heat-treated, and in the case of a yarn form, the compounds may be applied using a cheese dyeing machine or the like, or may be applied by a padding method or an exhaustion method using a dyeing machine after forming a woven or knitted fabric or nonwoven fabric. Preferably, when these compounds are incorporated into polyester fibers during or before the graft polymerization process, a modified fiber with a high graft polymerization rate can be realized, and the graft efficiency can be increased, which is expected to reduce chemical costs. More preferably, the compounds are added simultaneously during the graft polymerization process. Since these alkyl ester compounds are difficult to dissolve in water, when using an aqueous processing process, they may be dissolved in a polyester fiber carrier agent such as an orthophenylphenol (OPP)-based, chlorobenzene-based, or phthalimide-based carrier agent, and then dispersed in water together with the carrier agent. The amount of carrier agent used may be about 5 to 20 times the mass of these alkyl ester compounds.
[0019] The mass increase rate (graft polymerization rate) due to polymerization of the ethylenically unsaturated organic acid inside the fiber is preferably 5 to 60 mass%, more preferably 7 to 55 mass%, further preferably 10 to 50 mass%, and particularly preferably 20 to 45 mass%. If the graft polymerization rate is lower than the above range, the functionality such as moisture absorption and deodorization may not be fully exhibited. On the other hand, if the graft polymerization rate is higher than the above range, the color fastness tends to be easily reduced. The graft polymerization rate can be calculated from the mass increase rate of the bone dry mass (W1) of the fiber after graft polymerization and washing relative to the bone dry mass (W0) of the fiber before graft polymerization according to the following formula. Graft polymerization rate = (W1-W0) x 100 / W0
[0020] When the amount of raw material monomer used is the same, a higher graft polymerization rate means that the raw material monomer is used more efficiently and the chemical cost is reduced.
[0021] The graft polymerization method is not particularly limited, but a method of immersing polyester fibers in an aqueous emulsion containing a radical polymerization initiator, an N-alkylphthalimide compound, a surfactant, and an ethylenically unsaturated organic acid and heat-treating the fibers is preferred. By using this method, graft polymerization can be efficiently and uniformly performed, and deterioration of the physical properties of the fibers is reduced.
[0022] The concentration of the ethylenically unsaturated organic acid in the treatment bath for graft polymerization is preferably 1 to 100% owf (on the weight of fiber) based on the mass of the polyester fiber, more preferably 5 to 80% owf, and even more preferably 8 to 60% owf. When processing is performed at these monomer concentrations, it is usually possible to obtain a graft polymerization rate of 0.5 to 100% by mass. Within this range, the higher the monomer concentration, the higher the graft polymerization rate, and the higher the functionality tends to be.
[0023] Examples of the radical polymerization initiator include benzoyl peroxide (BPO), toluyl peroxide, aromatic alkyl peroxide compounds, dichlorobenzoyl peroxide, dicumyl peroxide, azobisisobutyronitrile, cumene hydroperoxide, perbenzoic acid, and perbenzoic acid esters. The amount of the radical polymerization initiator used is preferably about 0.1 to 10% owf based on the fiber mass. The radical polymerization initiator is preferably hydrophobic.
[0024] In the present invention, it is preferable to use a compound having carrier ability in order to promote the absorption of ethylenically unsaturated organic acids or to improve the dispersibility of initiators in water. As the compound having carrier ability, orthophenylphenol (OPP), chlorobenzene, phthalimide, and the like can be used. Phthalimide compounds are preferably used because they are easy to use and do not easily cause processing problems. The phthalimide compounds are compounds having a phthalimide group, and N-substituted phthalimide compounds having an aliphatic or aromatic alkyl group on the N group of phthalimide are preferable, and in consideration of the amount remaining in the product after processing, odor, safety, and handling, N-alkylphthalimide compounds having low molecular weight aliphatic alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, and isobutyl are more preferable. These compounds may be used alone or in combination. The amount of the phthalimide compound used in the graft polymerization bath is preferably 0.01% by mass or more and 4% by mass or less. From the viewpoints of safety, processing solution cost, and reactivity, it is more preferable to use 0.1% by mass or more and 1.0% by mass or less. If the amount is less than this range, the polymerization efficiency is likely to decrease, and even if the amount is increased beyond this range, the polymerization rate does not increase and an odor tends to remain.
[0025] To stabilize the graft polymerization treatment bath, surfactants such as nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic anionic surfactants, nonionic cationic surfactants, etc. These may be used alone or in combination of two or more in some cases, but from the standpoint of emulsion system stability and graft polymerization efficiency, it is preferable to use a nonionic surfactant, a nonionic anionic surfactant, or a mixture of a nonionic surfactant and an anionic surfactant.
[0026] When the polyester fiber is immersed and heat-treated during the graft polymerization treatment, the treatment conditions are usually 50° C. to 150° C. for 5 minutes to 3 hours, and preferably 70° C. to 130° C. for 30 minutes to 2 hours. The atmosphere during the treatment may be air, but it is preferable to replace the atmosphere with nitrogen gas and perform the treatment in a nitrogen gas atmosphere.
[0027] Fibers graft-polymerized with ethylenically unsaturated organic acids by these methods have acid carboxyl groups immediately after polymerization, but by treating them in a high pH bath to convert some of the acid end groups of the polymerized ethylenically unsaturated organic acids into alkali metal salts, the moisture absorption properties can be increased. It is also advisable to leave some of the acid end groups of the ethylenically unsaturated organic acids without converting them into alkali metal salts. The remaining acid end groups can provide strong ammonia deodorizing performance.
[0028] Examples of the metal salts used for this alkali metal chloride include lithium, sodium, potassium, etc., and examples of basic alkali metal compounds include alkali metal salts of inorganic weak acids such as sodium carbonate, potassium carbonate, dibasic sodium phosphate, tribasic sodium phosphate, etc., alkali metal salts of organic weak acids such as sodium acetate, sodium propionate, etc., and compounds that dissolve in water and exhibit alkalinity such as sodium sulfite and sodium silicate. These are used alone or as a mixture of two or more. In the present invention, the alkali metal compounds are preferably used at a concentration of less than 12 in the liquid pH. If an alkaline liquid with a high pH is used, the modified fiber will swell significantly, and the color fastness will decrease when dyed. For example, polyphosphates such as sodium tripolyphosphate are preferably used because they are easy to adjust the pH. It is preferable to use other weak alkaline salts for alkali metal hydroxides that become strong alkaline such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, since it is difficult to adjust the liquid pH in the weak alkaline range. It is preferable to generally carry out the alkali metal chloride treatment of graft-polymerized polyester fibers at a temperature in the range of room temperature to 100°C.
[0029] As the sequestering agent that may be used together with the above-mentioned alkali metal compound, known substances can be used. In general, the sequestering agent includes condensed phosphates such as sodium pyrophosphate, sodium triphosphate, sodium trimetaphosphate, sodium tetrametaphosphate, and sodium polyphosphate, ethylenediaminetetraacetic acid salts such as disodium salt of ethylenediaminetetraacetic acid, tetrasodium salt of ethylenediaminetetraacetic acid, diammonium salt of ethylenediaminetetraacetic acid, and tetraammonium salt of ethylenediaminetetraacetic acid, N-hydroxyethylethylenediamine-N,N'N'-triacetic acids, diethylenetriaminepentaacetic acid, glycol ether diamine tetraacetic acid, cyclohexane diamine tetraacetic acid, and nitrilotriacetic acids. The amount of these sequestering agents used depends on the amount of polyvalent metal ions dissolved in the water, but is generally in a concentration of 0.01 g / L to 5 g / L.
[0030] The modified polyester fiber obtained by the above method has a moisture absorption rate of 3 to 30%, further 5 to 30%, and further 9 to 30% in a 20°C x 65% RH environment, and can have high deodorizing performance against basic odors such as ammonia and acidic odors such as acetic acid. In this case, the ammonia deodorizing performance refers to a performance in which ammonia water is dropped into a 5L plastic container to a concentration of 100 ppm, a 10 cm x 10 cm sample is placed in the plastic container, and the ammonia concentration in the plastic container after 120 minutes is 30 ppm or less after sealing. The ammonia concentration is measured using a gas detector tube manufactured by Gastec Co., Ltd. If the ammonia concentration is higher than 30 ppm after 120 minutes, the odor absorption in actual use is insufficient, and it cannot be said to have sufficient ammonia deodorizing performance.
[0031] Specifically, the modified polyester fiber of the present invention can satisfy the following deodorizing performances for acetic acid, isovaleric acid, and ammonia: acetic acid deodorizing rate ≧90%, isovaleric acid ≧90%, and ammonia deodorizing rate ≧90%. More preferably, the modified polyester fiber can satisfy the following deodorizing rates for acetic acid ≧95%, isovaleric acid ≧95%, and ammonia deodorizing rate ≧95%.
[0032] In order to stably exert the functionality such as moisture absorption and deodorization of the modified polyester fiber of the present invention, it is preferable to control the pH of the fiber itself after dyeing. The extraction pH in the finishing of the textile product using the modified polyester fiber of the present invention is adjusted to a lower limit of 4 or more, preferably 4.5 or more, more preferably 6 or more, and an upper limit of 10 or less, preferably 8.9 or less, more preferably 7.9 or less. If the extraction pH is below the above range, the functionality such as moisture absorption and deodorization is likely to decrease, and if the extraction pH exceeds the above range, the dye fastness is likely to decrease. By adjusting the extraction pH to a specific range in this way, it is possible to suppress the decrease in dye fastness even if the graft polymerization rate is increased to more than 10% by mass, although in the past, if the graft polymerization rate exceeded 10% by mass, the wet dye fastness such as friction fastness and washing fastness was likely to decrease and practical use was not possible. To adjust the extraction pH of the fiber to the above range, for example, a basic alkali metal compound that makes the aqueous solution alkaline is used to adjust the treatment bath to an acidic to weakly alkaline bath with a pH of less than 12, and the textile product is immersed in the treatment bath. Specifically, the pH of the final washing solution and / or the finishing solution after dyeing is preferably adjusted to 5 to 10, more preferably 5.5 to 9. This is to control the extraction pH of the product within the above range (weakly acidic to weakly alkaline). Note that a sequestering agent may be added to remove Ca ions and Mg ions from this treatment bath, or conversely, divalent or trivalent metal ions may be added.
[0033] The textile products using the modified polyester fiber of the present invention may be in any form, such as cotton, tow, thread, woven fabric, knitted fabric, nonwoven fabric, etc. In addition, textile products also include dyed products such as clothing, bedding, interior goods, and other accessories sewn using the same.
[0034] The blending ratio of the modified polyester fiber of the present invention in the textile product is preferably 5% by mass or more based on the total fiber mass. This allows a significant difference in functionality such as moisture absorption and deodorization to be obtained compared to textile products made only of unmodified fibers. The blending ratio is preferably 10 to 100% by mass, more preferably 20 to 100% by mass. If the blending ratio is low, the functional effect of the modified polyester fiber is less likely to be exhibited in the textile product. The textile product may contain, as components other than the modified polyester fiber, polyester fibers such as polyethylene terephthalate fibers, polybutylene terephthalate fibers, and polylactic acid fibers; polyamide fibers such as nylon 6 and nylon 66; regenerated fibers such as rayon, polynosic, cupra, and lyocell; semi-synthetic fibers such as acetate fibers and triacetate fibers; and natural fibers such as cotton. These fibers may be modified or unmodified.
[0035] The textile product of the present invention can be made of only modified polyester fibers, but it is preferable to mix unmodified polyester fibers or other fibers in view of production costs and quality improvement of spun yarns, etc. For example, in the case of a textile product made of 100% polyester, if the moisture absorption rate of the entire textile product is 1.0% or more in an environment of 20°C x 65% RH, the difference in moisture absorption can be felt compared to unmodified polyester textile products. It is preferable to adjust the mixing ratio of modified polyester fibers so that the moisture absorption rate is more preferably 1.5% or more, and even more preferably 3% or more.
[0036] When the fiber product of the present invention is adjusted from weakly acidic to weakly alkaline, various functionalities are expressed in a well-balanced manner, and since the fabric pH does not change much due to home washing, the performance change after washing is small. However, if high moisture absorption is required, it is preferable to increase the pH of the fiber to about 10.
[0037] The modified polyester fiber of the present invention has both high moisture absorption and deodorizing properties, and can improve the stickiness and sultryness that have been problems when using conventional polyester fibers. In addition, it has high sweat deodorizing properties and moderate pH balance, so it can reduce the unpleasant feeling of sweat odor caused by sweating and pH changes on the skin surface. In addition, the fiber product of the present invention is particularly excellent in deodorizing ammonia odor, so it is suitable not only for clothing but also for living materials, interior decorations, pet products, etc. The modified polyester fiber of the present invention also has excellent washing durability, and can continue to enjoy high moisture absorption and deodorizing properties throughout the product life. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0039] <Graft polymerization rate> The mass increase rate was calculated from the absolute dry mass (W1) of the fiber after graft polymerization and washing relative to the absolute dry mass (W0) of the fiber before graft polymerization according to the following formula. Graft polymerization rate = (W1-W0) x 100 / W0 The absolute dry mass is the dry mass measured after drying for 4 hours in a hot air dryer at 120° C. and then slowly cooling to room temperature in a desiccator containing silica gel.
[0040] <Quantitative method for TMPDB and TMPMB contained in fibers> Approximately 0.1 g of sample was weighed and ultrasonically extracted (60 min x 3 times) with 30 mL of chloroform. Each extract was measured by GCMS to quantify TMPDB and TMPMB. The m / z 71 extracted ion chromatogram of the standard solution in which TMPDB and TMPMB standards were diluted with chloroform was measured, a calibration curve was created, and the contents of TMPDB and TMPMB for each sample solution were calculated using the regression equation of the calibration curve. For reference, the calibration curve for standard TMPDB is shown in Figure 1. (Standard solution concentration: peak area value 0.107 μg / ml: area 8645, 1.07 μg / ml: area 87906, 10.67 μg / ml: area 939878) Note that for TMPMB, two peaks were detected as an isomer mixture in the measurement of the standard solution, so the total amount of the two isomers was calculated. (GCMS analysis conditions) Apparatus: Agilent Technologies HP-7890 / HP-5975 (Agilent), column: Rxi-1ms (length 30 m, inner diameter 0.25 mm, film thickness 1.0 μm), injection port temperature: 280 °C, column flow rate: 1 mL / min, split ratio: 10, column oven temperature: 50 °C (2 min) - 280 °C (15 min), 15 °C / min, MS measurement mode: SIM, TMPDB (43, 56, 71), TMPMB (43, 56, 71) Quantitative ion: m / z 71
[0041] <Moisture absorption rate> The bone dry mass (S0) of the textile product was determined, and then the mass (S1) of the textile product after leaving it in a standard environment (20°C x 65% relative humidity) for 48 hours was determined. The moisture absorption rate was calculated from the mass increase from these values. Moisture absorption rate (mass%)=(S1-S0)×100 / S0
[0042] <Graft fiber mixing ratio> When polyester fibers were mixed with fibers other than polyester, fiber identification and fiber blend ratio were determined according to JIS-L1030. When normal polyester fibers and modified polyester fibers were mixed, if separation was possible based on color or fiber appearance (thickness, cross section, gloss, etc.), a magnifying glass was used to separate the fibers. If separation based on color or appearance was not possible, the modified fibers were dyed at room temperature using a cationic dye, and then separated using a magnifying glass. The separated modified fibers were then repeatedly washed in hot water and water with an 80°C acetic acid solution until no more dye was eluted, and then left to stand under standard conditions until the equilibrium moisture content was reached, and the blend ratio was determined by measuring the mass.
[0043] <Friction fastness> Measurements were taken using a JIS-L0849 friction tester II type (Gakushin type). The attached white cloth was used under dry / wet conditions in accordance with the JIS-L0849 regulations, and the staining was graded.
[0044] <pH of the extract> JIS-L1096:2020 8.37 pH of extract was measured based on A method (JIS method).
[0045] <Ammonia deodorization rate> A 10cm x 10cm woven or knitted fabric was placed in a Tedlar bag (made of polyvinylidene fluoride film) and sealed, and ammonia was added to the bag to a concentration of 100 ppm. After leaving the bag for 120 minutes, the ammonia concentration was measured using a gas detector. The ammonia deodorization rate was calculated from the rate of decrease in concentration.
[0046] <Acetic acid deodorization rate> A 10cm x 10cm woven or knitted fabric was placed in a Tedlar bag (made of polyvinylidene fluoride film) and sealed, and acetic acid was added to the bag to a concentration of 50 ppm. After leaving the bag for 120 minutes, the acetic acid concentration was measured using a gas detector. The deodorization rate of acetic acid was calculated from the rate of decrease in concentration.
[0047] <Isovaleric acid deodorizing rate> The woven / knitted fabric (6cm x 8cm) was placed in a Tedlar bag (made of polyvinylidene fluoride film) and sealed, and 2L of nitrogen gas was added. After that, isovaleric acid was added to the bag so that the concentration was about 38ppm, and after leaving the bag for 120 minutes, the concentration of isovaleric acid was measured by gas chromatography. The deodorizing rate of isovaleric acid was calculated from the rate of decrease in concentration.
[0048] Example 1 Polyethylene terephthalate (intrinsic viscosity 0.633) was spun at a polymer temperature of 288°C and a spinning speed of 1600 m / min using a hollow round cross section fiber spinning nozzle. The fiber was then stretched at a stretching temperature of 112°C, a stretch ratio of 2.32, and a stretching speed of 140 m / min, and crimped to form cut fibers. The obtained polyester staple fiber with a hollow cross section had a fineness of 6.5 dtex and a cut length of 64 mm.
[0049] Next, the polyester staple fiber was scoured and washed using an Obermeyer dyeing machine, and then graft-polymerized according to the following formula 1 to produce modified fiber 1. After washing with hot water, the fiber was treated with 1 g / L of soda ash solution at 60°C for 10 minutes, and then washed with ion-exchanged water to adjust the fiber extraction pH to 7.9 to 8.1. The fiber was then oiled and extracted. The graft polymerization rate of modified fiber 1 was 30% by mass. (Formulation 1) 99% methacrylic acid 40% owf, benzoyl peroxide (75% moisture content) 0.8% owf, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB) 0.4% owf, chelating agent (nitrilotriacetic acid, disodium) 0.5g / L, carrier agent (N-butylphthalimide) 5g / L, nonionic dispersant 1% owf, soda ash to adjust the pH of the treatment solution to 3.2. Bath ratio 1:10, treatment temperature 105℃, treatment time 90 minutes
[0050] Subsequently, 30% by mass of modified fiber 1 and 70% by mass of unmodified fiber before modification were weighed and mixed, and the mixture was uniformly mixed to prepare a filling for a pillow. The evaluation results of modified fiber 1 and filling in Example 1 are shown in Table 1. In addition, the m / z71 extracted ion chromatogram for calculating the TMPDB content of modified fiber 1 is shown in FIG. 2.
[0051] Example 2 Except for changing the concentration of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB) in formulation 1 to 0.1% owf, graft polymerization was performed in the same manner as in Example 1 to produce modified fiber 2 and padding. The evaluation results of modified fiber 2 and padding in Example 2 are shown in Table 1.
[0052] Example 3 Except for changing the concentration of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB) in formulation 1 to 2.5% owf, graft polymerization was performed in the same manner as in Example 1 to produce modified fiber 3 and padding. The evaluation results of modified fiber 3 and padding in Example 3 are shown in Table 1.
[0053] Example 4 Except for changing the methacrylic acid in Formulation 1 to acrylic acid, the graft polymerization treatment was carried out in the same manner as in Example 1 to prepare modified fiber 4 and padding. The evaluation results of modified fiber 4 and padding in Example 4 are shown in Table 1.
[0054] Example 5 Except for changing the concentration of methacrylic acid in Formulation 1 to 10% owf, the graft polymerization treatment was carried out in the same manner as in Example 1 to prepare modified fiber 5 and padding. The evaluation results of modified fiber 5 and padding in Example 5 are shown in Table 1.
[0055] Example 6 Except for changing 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB) in formulation 1 to 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TMPMB), graft polymerization was carried out in the same manner as in Example 1 to produce modified fiber 6 and padding. The evaluation results of modified fiber 6 and padding in Example 6 are shown in Table 1.
[0056] Example 7 Polyethylene terephthalate was replaced with polytrimethylene terephthalate (intrinsic viscosity 0.95), and the polymer temperature was changed to 265°C for spinning. A hollow cross-section polyester staple fiber (fineness 6.5 dtex, cut length 64 mm) was obtained in the same manner as in Example 1. This staple fiber was subjected to graft polymerization treatment according to formulation 1 in the same manner as in Example 1 to produce modified fiber 7 and padding. The evaluation results of modified fiber 7 and padding in Example 7 are shown in Table 1.
[0057] Example 8 The polyester staple fiber treated with Formulation 1 was treated with 10 g / L of caustic soda solution instead of soda ash at 40°C for 10 minutes, and then washed with ion-exchanged water to adjust the fiber extraction pH to 9.8 to produce Modified Fiber 8 and filling. The evaluation results of Modified Fiber 8 and filling of Example 8 are shown in Table 1.
[0058] Example 9 Except for changing 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB) in formulation 1 to di-2-ethylhexyl phthalate (DEHP), graft polymerization was carried out in the same manner as in Example 1 to produce modified fiber 9 and padding. The evaluation results of modified fiber 9 and padding in Example 9 are shown in Table 1.
[0059] Example 10 Except for changing the concentration of methacrylic acid in Formulation 1 to 55% owf, the graft polymerization treatment was carried out in the same manner as in Example 1 to prepare modified fiber 10 and padding. The evaluation results of modified fiber 10 and padding in Example 10 are shown in Table 1.
[0060] Comparative Example 1 The modified fiber 11 and the filling were prepared in the same manner as in Example 1, except that the formulation 1 in Example 1 was used without adding 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TMPDB). The evaluation results of the modified fiber 11 and the filling in Comparative Example 1 are shown in Table 1.
[0061] Comparative Example 2 In Example 1, unmodified polyester staple fibers and filling were prepared without treatment with Formulation 1. The evaluation results of the unmodified fibers and filling of Comparative Example 2 are shown in Table 1.
[0062] [Table 1]
[0063] As can be seen from Table 1, the padding using the modified polyester fiber of Examples 1 to 10 containing a specific alkyl ester compound showed extremely high moisture absorption rate and deodorizing properties, but the padding using the modified polyester fiber of Comparative Example 1 not containing an alkyl ester compound had a clearly low graft polymerization rate, despite the processing concentration of methacrylic acid (ethylenically unsaturated organic acid) being the same as that of Example 1, and was significantly inferior in moisture absorption rate and deodorizing rate against isovaleric acid compared to Example 1. In addition, the padding using the unmodified polyester fiber of Comparative Example 2 was significantly inferior in moisture absorption rate and deodorizing rate against acetic acid, isovaleric acid, and ammonia compared to Example 1. [Industrial Applicability]
[0064] The modified polyester fiber of the present invention has achieved modification through a high graft polymerization rate and improved functionality such as deodorizing properties due to the specific alkyl ester compound, and is therefore extremely useful in fields that handle various types of textile products.
Claims
1. A modified polyester fiber, which is a polyester fiber in which an ethylenically unsaturated organic acid is polymerized inside the fiber, and which contains 25 to 10,000 ppm of an alkyl ester compound of an aliphatic carboxylic acid and / or an aromatic carboxylic acid.
2. 2. The modified polyester fiber according to claim 1, wherein the ethylenically unsaturated organic acid is (meth)acrylic acid.
3. The modified polyester fiber according to claim 1, characterized in that the alkyl ester compound is at least one compound selected from the group consisting of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, and di-2-ethylhexyl phthalate.
4. The modified polyester fiber according to claim 1, characterized in that the ethylenically unsaturated organic acid is polymerized inside the fiber so that the mass increase rate due to polymerization is 5 to 60 mass %.
5. 2. The modified polyester fiber according to claim 1, characterized in that the extraction pH is 4 to 10.
6. The modified polyester fiber according to claim 1, characterized in that the moisture absorption rate in an environment of 20°C and 65% RH is 3 to 30%.
7. 2. The modified polyester fiber according to claim 1, characterized in that the deodorizing rate of acetic acid is ≧90%, the deodorizing rate of isovaleric acid is ≧90%, and the deodorizing rate of ammonia is ≧90%.
8. A textile product comprising 5% by mass or more of the modified polyester fiber according to any one of claims 1 to 7.
Citation Information
Patent Citations
Modified polyester fiber and method for producing the same
JP2002069844A
Fiber product containing modified fiber
JP2017014641A